2014
DOI: 10.1177/1545968314552528
|View full text |Cite
|
Sign up to set email alerts
|

Walking Speed and Step Length Asymmetry Modify the Energy Cost of Walking After Stroke

Abstract: Background A higher energy cost of walking poststroke has been linked to reduced walking performance and reduced participation in the community. Objective To determine the contribution of post-intervention improvements in walking speed and spatiotemporal gait asymmetry to the reduction of the energy cost of walking after stroke. Methods Forty-two subjects with chronic hemiparesis (> 6 months poststroke) were recruited to participate in 12 weeks of walking rehabilitation. The energy cost of walking, walking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
167
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(181 citation statements)
references
References 35 publications
8
167
6
Order By: Relevance
“…Therefore, a decreased gait symmetry interferes with efficient gait performance (Mudge &Stott, 2009), andAwad et al (2015) further reported on the significant relationship between gait symmetry and the energy cost during walking in stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a decreased gait symmetry interferes with efficient gait performance (Mudge &Stott, 2009), andAwad et al (2015) further reported on the significant relationship between gait symmetry and the energy cost during walking in stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that step length asymmetry has negative functional consequences after stroke. Step length asymmetry is associated with reduced forward propulsion, slow walking speed and reduced dynamic balance (Balasubramanian et al, 2007; Bowden et al, 2006; Patterson et al, 2010), as well as an increased energy cost of walking (Awad et al, 2014; Mattes et al, 2000). Other evidence has shown that muscle activation in one leg directly facilitates out-of-phase muscle activation in the contralateral leg during cycling, thereby facilitating smooth reciprocal and symmetric timing of leg movement (Kautz et al, 2002; Ting et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Still the screening must be meticulous and the treatment must be early initiated, so that the program yields the best response with the lowest cost possible. 19 We emphasize that, after the hospital discharge of the stroke patients, the referrals to rehabilitation programs must be done the earliest possible. However, due to precarious health systems in developing countries, such as Brazil, these patients rarely initiate the rehabilitation program short after the stroke event.…”
Section: 13mentioning
confidence: 99%